Sliding Mode Control Design For Prosthetic Hand System - Jali, Mohd Hafiz; Ghazali, Rozaimi; Soon, Chong Chee; Muhammad, Ahmad Razif (Asian Research Publishing Network (ARPN), 2021)
This paper describes the Sliding Mode Controller (SMC) for the Prosthetic Hand System. There are different nonlinear controls theories, as for example the SMC approach; it has proved sound and well-established literature. Recently prosthetic hands turn out to be more significance since its capability to be potential substitute hand for an amputee. By utilizing a different kind of actuators, prosthetic hands become more practical as it could work with neuro motors energy which started by the Automatic Nervous System (ANS) of the brain. However, the mathematical modelling of the system should be fittingly resolved to guarantee the precision of the controller design. Then, the system needs to be designed based on the theory of the Lyapunov stability and the control rules of the SMC through the MATLAB/Simulink software. The results accomplished affirm reasonable specialized means and synthesis by using sliding modes for nonlinear control tasks. Then the performance of the system is validated and verified via simulation environment. By referring to the results obtained, it can be concluded that the SMC capable of reducing the controller effort while enhancing the Prosthetic Hand performance